Effectiveness of Patient Centered Care to Reduce Anxiety Level and Improve Satisfaction in Patients Undergoing Cataract Surgery - Mochammad Sjarifudhin; Elsye Maria Rosa (Universitas Muhammadiyah Yogyakarta, 2018)
Research on Patient Centered Care (PCC) in cataract patients is still limited, especially those that analyze the effectiveness of PCC in reducing anxiety levels and improving the patient satisfaction. This study was a quasi-experimental pre- and post-test design, which involved 30 treatment respondents and 30 control respondents. The instrument used a SAI questionnaire to measure anxiety and SERVQUAL modifications to measure patient satisfaction. The study was conducted at Nganjuk Eye Clinic in October-November 2018. Analysis of data using paired t-test and independent t-test. The results of difference tests of anxiety levels before and after PCC and difference tests of anxiety levels of the control and PCC group showed the results of sig. 2-tailed = 0,000. Whereas the difference tests of satisfaction levels between the control and PCC group were obtained sig. 2-tailed = 0.035. The PCC Effect Size obtained strong effects (2.59 and 4.31) in reducing anxiety and average effect (0.56) on improving satisfaction. There were significant differences in the level of anxiety and satisfaction in both groups. The results showed that PCC was very effective in reducing anxiety levels and quite effective in improving the satisfaction on cataract surgery patients.